A Closer Look at OECD Statistic - Charbonnier, Eric (International Higher Education, 2009)
Education at a Glance is the annual result of a long collaboration between governments of OECD countries, experts, and institutions that participate in the Indicators of Education Systems program of the Organization for Economic Cooperation and Development (OECD). This article is an respond to the article on "Taking a Closer Look at the OECD Tertiary Statistics" by Arthur Hauptman. The following topics are covered in this article: International students and enrollment ratio, indicators to interpret the results, private funding and R&D, relationship between criteria and outcomes, and strategies for investing in expanding education systems.